UiTM vehicle management system (UVMS) - Ismail @ Mansor, Mohd Zulhilmi (2014)
Unit Kenderaan is a leading provider of transportation facilities for all indoor and outdoor activities. Apart from the students and staff of UITM Shah Alam, Unit Kenderaan also helps students and staff of UITM branch campus, especially in Sabah and Sarawak coming by plane or require services in Shah Alam. Unit Kenderaan carries the responsibility to provide the transport facility to students and staff systematically through campus vehicle to ensure effective and efficient service. Currently, in order to apply for the transport from Unit Kenderaan, the applicant has to reserve the vehicle manually. First they have to fill in the form and submit it at the counter. Two days after submission, the applicant has to confirm for the approval of the application at the counter. If the application is rejected, the procedure need to be repeated again. Since this procedure seems to be so complicated, UITM Vehicle Management System (UVMS) has been developed. UVMS is a web based application that uses online booking system which is believed will increase the efficiency and productivity of current system used for transportation reservation at Unit Kenderaan. In developing this system, project methodology framework based on rapid application development (RAD) model is applied. RAD employs the construction of prototypes which is divided into four phases starting with requirements planning, user design, and construction and finally ends with cutover. Requirements planning comprises of the problem identifying, data collection, plan project execution duration and identification of user requirements. Next step is user design where database and interface are designed based on user requirements. The construction phase involves the development of UVMS using PHP as programming language and MySQL as database. Finally the UVMS is demonstrated in the cutover phase. The development of UVMS requires hardware tools consist of windows 7 ultimate, MySQL, PHP, adobe Photoshop and others that will be described in analysis and discussion section. Further details and explanation of UVMS are described briefly in this report.